Private HE in Bangladesh: the impact on HE governance & legislation - Alam, Gazi M. (2007)
Although it is claimed that private education is a recent phenomenon in the developing world, criteria of private educations and their schemata have evolved out of historical practices. The introduction of private education in South Asia was implemented by a process known as 'Gru-Shiso'. An individual with a good analytical knowledge was considered as `Gru' and his or her followers were known as 'Shiso'. Exercising knowledge through Gru-Shiso had always been a fundamental part of education in Bangladesh. With the gradual increase of demand for education in contemporary Bangladesh, there has been an increase in private education provision though most acknowledge that education should be the fundamental concern of public policy.